2021
DOI: 10.1002/cncy.22501
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of programmed death ligand 1 expression in cytology to determine eligibility for immune checkpoint inhibitor therapy in patients with head and neck squamous cell carcinoma

Abstract: BACKGROUND:Immune checkpoint inhibitors targeting the programmed cell death protein 1 (PD-1)/programmed cell death ligand 1 (PD-L1) pathway have recently emerged as a frontline treatment for head and neck squamous cell carcinoma (HNSCC). The evaluation of PD-L1 expression by immunohistochemistry in histologic samples is used to determine the eligibility of patients with HNSCC for immunotherapy. Patients with newly diagnosed HNSCC are frequently diagnosed by fine-needle aspiration (FNA) of lymph nodes with meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…As opposed to TPS assessment, the evaluation of PD-L1 expression using CPS has not been well established on cytological material, mainly because of challenges in identifying tumor-associated immune cells in the absence of tissue architecture. Although still limited, the literature data showed that the evaluation of CPS on cytological samples is feasible, especially in the case of positive PD-L1 expression [ 93 , 94 ].…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to TPS assessment, the evaluation of PD-L1 expression using CPS has not been well established on cytological material, mainly because of challenges in identifying tumor-associated immune cells in the absence of tissue architecture. Although still limited, the literature data showed that the evaluation of CPS on cytological samples is feasible, especially in the case of positive PD-L1 expression [ 93 , 94 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Liu et al . proposed that the expression of PD-L1 in HNSCC cytology samples is highly consistent with matched histological samples ( Liu et al, 2021 ). Lee et al also believe that ICIs show good anti-tumor activity against R/M HNSCC ( Lee et al, 2021 ).…”
Section: Adenine-related Rna Modifications and Head And Neck Squamous Cell Carcinoma Therapymentioning
confidence: 85%
“…Blocking TIGIT/CD155 combined with PD-L1 monoclonal antibody treatment can significantly improve the efficacy of HNSCC (Mao et al, 2021). Meanwhile, Liu et al proposed that the expression of PD-L1 in HNSCC cytology samples is highly consistent with matched histological samples (Liu et al, 2021). Lee et al also believe that ICIs show good anti-tumor activity against R/M HNSCC (Lee et al, 2021).…”
Section: Adenine-related Rna Modifications and Head And Neck Squamous Cell Carcinoma Therapymentioning
confidence: 99%
“…The majority of the specimens in our review were non‐small cell lung adenocarcinomas, the review studies contained 23 melanomas, 9 21 squamous cell carcinomas of the head and neck, 10 24 cases of ovarian adenocarcinoma, 11 39 pancreatic carcinomas, 12 and 79 squamous cell carcinomas of the lung 13 …”
Section: Resultsmentioning
confidence: 99%